Resource Leveling Optimization Using Different Objective Functions on Building Project - Irvania, Artya; Pujiraharjo, Alwafi; Suharyanto, Agus (ASTONJADRO, 2024)
One of the problems that often occur in allocating labor is fluctuations arising from the uneven allocation of labor, so resource leveling optimization is needed to avoid these problems. This study investigates the impact of five objective functions to determine which objective function can produce an efficient labor histogram and determine the effect of resource leveling on changes in labor cost fluctuations based on case studies. The research was conducted using the symbiotic organisms search (SOS) algorithm. The results of this study show that objective function 4 (the minimum amount of the sum of the squared deviations in the use of resources between time intervals) is more effective than other objective functions by producing the most significant average increase in fitness value of 61.64% and can produce a smoother labor allocation histogram compared to other objective functions. Resource leveling also affects cost fluctuations, with a decrease in efficiency of 47%, so that it can improve project implementation efficiency and effectiveness.